The Influence of Service Quality and Customer Satisfaction on Customer Loyalty Pos Kupi Langsa - Merdekawati, Intan (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The current era of globalisation has led to the growth of various new industries, including business industries that arise from the creativity and innovation of their owners. Starting from the need for food, drinks, clothing, stationery, transportation, to the need for the fulfilment of selfish desires. This opportunity then creates humans who are more creative in thinking and working. This creativity is then applied by some people in doing business. Purpose. This study aims to determine and analyze the effect of Responsiveness, Assurance, Physical Evidence, Empathy, Reliability, and Customer Satisfaction on Omeycak Coffee's Customer Loyalty. Method. This research is a combination of quantitative and qualitative research, which is a social research that fundamentally relies on observing humans in their own area and dealing with these people who seek to reveal the actual facts / phenomena that occur in the field and then collaborate with data to support the success of the research.. Results. The results showed that simultaneously, Responsiveness, Assurance, Physical Evidence, Empathy, Reliability, and Customer Satisfaction had a significant effect on Customer Loyalty at Pos Kupi Langsa. Partially Responsiveness, Assurance, Physical Evidence, Empathy, Reliability, and Customer Satisfaction each have a positive and significant effect on Customer Loyalty. Conclusion. The conclusion of this study is that Responsiveness, Assurance, Physical Evidence, Empathy and Reliability simultaneously have a significant effect on Customer Loyalty. Responsiveness has a positive and significant effect on Pos Kupi Customer Loyalty. Guarantee has a positive and significant effect on Pos Kupi Customer Loyalty. Physical Evidence has a positive and significant effect on Pos Kupi Customer Loyalty. Empathy has a positive and significant effect on Pos Kupi Customer Loyalty. Reliability has a positive and significant effect on Pos Kupi Customer Loyalty. Customer Satisfaction has a positive and significant effect on Pos Kupi Customer Loyalty.